The Impact of Firearm Levels on Homicide Rates: the Effects of Controlling for Cultural Differences in Cross-National Research - Kovandzic, Tomislav (American journal of criminal justice, 2022)
We analyze the largest set of nations (n = 55) with a valid measure of gun ownership levels ever used to test the effect of national gun levels on homicide rates. We control for measures of national culture to better isolate the effects of firearm availability. We find that, while national gun levels have a significant positive bivariate correlation with homicide rates, once one controls for violence-related cultural differences between nations, the association disappears. With this larger, more diverse set of nations, the U.S. is not influential - gun levels are unrelated to homicide rates regardless of whether it is included in the analysis.